2021
DOI: 10.3390/cancers13164047
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Plasma Cell Contamination of Peripheral Blood Stem Cell Autografts, Assessed by Next-Generation Flow Cytometry, Is a Negative Predictor for Deep Response Post Autologous Transplantation in Multiple Myeloma; A Prospective Study in 199 Patients

Abstract: High-dose chemotherapy with autologous stem cell support (ASCT) is the standard of care for eligible newly diagnosed Multiple Myeloma (MM) patients. Stem cell graft contamination by aberrant plasma cells (APCs) has been considered a possible predictive marker of subsequent clinical outcome, but the limited reports to date present unclear conclusions. We prospectively estimated the frequency of graft contamination using highly sensitive next-generation flow cytometry and evaluated its clinical impact in 199 mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…PCL patients were treated with various regimens. NDMM patients, evaluated for the presence of CPCs (n = 161, see below for details), were treated with either bortezomib, lenalidomide, dexamethasone (VRD) or bortezomib, cyclophosphamide, or dexamethasone (VCD) as induction regimens followed by high-dose melphalan (HDM) with autologous stem cell transplantation (ASCT), according to the protocol described in detail elsewhere [ 16 ]. The number of CPCs and the proportion of patients bearing high-risk aberrations were equally distributed between the two treatment groups (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…PCL patients were treated with various regimens. NDMM patients, evaluated for the presence of CPCs (n = 161, see below for details), were treated with either bortezomib, lenalidomide, dexamethasone (VRD) or bortezomib, cyclophosphamide, or dexamethasone (VCD) as induction regimens followed by high-dose melphalan (HDM) with autologous stem cell transplantation (ASCT), according to the protocol described in detail elsewhere [ 16 ]. The number of CPCs and the proportion of patients bearing high-risk aberrations were equally distributed between the two treatment groups (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of IP is also of additional significance because the collection of stem cells occurs during this time. A recent, prospective study showed MM cells in 40% of the collected stem cells, with the frequency of contamination and re-infusion directly correlating with the post-induction response and conferring a 2-fold risk increase in not achieving or delaying CR post-HDT/ASCT ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the MASTER trial, the MRD negativity rate after D-KRd induction therapy was lower in patients with UHRCAs than in the other CA groups, indicating that the myeloma cells are more frequently contaminated in the former than in the latter [6]. In two clinical studies, the MRD status of the autograft correlated with the survival time after ASCT [49,50]. Therefore, we discuss the role of MRD eradication in autografts in achieving persistent MRD negativity, particularly in patients with UHRCAs.…”
Section: Mrd In Autografts Might Predict Clinical Outcomementioning
confidence: 96%